Evaluation of a novel pad printing technique for the fabrication of disposable electrode assemblies - Mooring, L; Karousos, N; Livingstone, C; Davis, J; Wildgoose, G; Wilkins, S; Compton, R (2005)
The viability of using a pad printing technique for the production of disposable electrode systems has been assessed. The morphology and structural characteristics of the carbon ink layers has been characterised and the electrochemical behaviour of the resulting layers investigated using a number of model systems. Voltammetric and potentiometric methodologies (in aqueous buffer and acetonitrile) were conducted using ferrocence carboxylic acid and naphthoquinone-thiol systems. The ability to create modified electrode assemblies through the incorporation of indicators directly within the ink prior to printing has been shown to provide a facile means through which the selectivity of the electrodes can be enhanced and provides a quick means of prototyping reagentless sensors. © 2004 Elsevier B.V. All rights reserved.